ARTIFICIAL INTELLIGENCE IN COLLEGE MATHEMATICS EDUCATION IN INDONESIA: A SYSTEMATIC REVIEW (International Journal of Food and Nutritional Sciences, 2022)
This systematic literature review aims to explore the current state of artificial intelligence (AI) implementation in college mathematics education in Indonesia. By examining relevant studies, this review provides an overview of the key applications, benefits, challenges, and future prospects of AI in mathematics education. The findings suggest that AI has the potential to enhance teaching and learning experiences, improve student engagement, and facilitate personalized learning in mathematics education. However, challenges such as limited access to technology, lack of teacher training, and ethical considerations need to be addressed to fully harness the benefits of AI in this context.